Tyrosol ameliorates lipopolysaccharide-induced ocular inflammation in rats via inhibition of nuclear factor (NF)-κB activation - SATO, Kazuaki (J Vet Med Sci, 2016)
We evaluated the anti-inflammatory effect of tyrosol (Tyr) on endotoxin-induced uveitis (EIU) in rats. EIU was induced in male Lewis rats by subcutaneous injection of lipopolysaccharide (LPS). Tyr (10, 50 or 100 mg/kg) was intravenously injected 2 hr before, simultaneously and 2 hr after LPS injection. The aqueous humor (AqH) was collected 24 hr after LPS injection; the infiltrating cell number, protein concentration, and tumor necrosis factor (TNF)-α, prostaglandin (PG)-E2 and nitric oxide (NO) levels were determined. Histopathologic examination and immunohistochemical studies for nuclear factor (NF)-κB, inhibitor of κB (IκB)-α, cyclooxygenase (COX)-2 and inducible NO synthase (iNOS) in the iris–ciliary body (ICB) were performed at 3 or 24 hr after LPS injection. To further clarify the anti-inflammatory effects, RAW264.7 macrophages were stimulated with LPS in the presence or absence of Tyr. Tyr reduced, in a dose-dependent manner, the infiltrating cell number, protein concentration, and TNF-α, PGE2 and NO levels in AqH and improved histopathologic scores of EIU. Tyr also inhibited LPS-induced COX-2 and iNOS expression, IκB-α degradation and nuclear translocation of activated NF-κB in ICB. Tyr significantly suppressed inflammatory mediator production in the culture medium and COX-2 and iNOS expression and activated NF-κB translocation in LPS-stimulated RAW264.7 cells. These results suggest that Tyr suppresses ocular inflammation of EIU by inhibiting NF-κB activation and subsequent proinflammatory mediator production.